La productiva introducción del espacio en el análisis de las confrontaciones políticas. Apuntes sobre el movimiento de desocupados en la Argentina reciente - Armesto, Melchor (Política y Sociedad, 2006)
It has been only recently that researchers on social movements have incorporated «spatial perspectives» in the analysis of contentious politics. Within this research field, this paper describes some «spatial dynamics» of the unemployed workers’movement in Argentina. Specifically, the paper deals with the relationship between space and road blockade. I argue that the emergence, diffusion and characteristics of road-blocking activities indicate that (a), the way in which certain social, economic and political changes influence spatial distributions and the scenarios of day-to-day routines of groups and individuals are enable and constrained by, up to a certain point, changes in the repertoire of contention, and, (b), as space is a historical and socially constructed object, it is both the context and the outcame of contentious politics. The strategic meaning of road blockade as spatial practice is to be found within their capacity for altering other basic spatial routines; and their political meaning is entangled with the territorial activities developed by the unemployed workers’movements within the «barrios».